CPW-Fed Slot Antenna for Wideband Applications - T. Shanmuganantham; K. Balamanikandan; S. Raghavan (International Journal of Antennas and Propagation)
A new coplanar waveguide (CPW)-fed wideband printed slot antenna is presented, and the impedance characteristics of this antenna with different sizes of tapers are discussed. The effect of tapering angle with the resonant frequency is also observed. The fundamental parameters of the antenna such as bandwidth, return loss, gain, radiation pattern, and polarization are obtained. All meets the acceptable antenna standards. The measured input impedance bandwidth (return loss < −10 dB) of the prototype antenna is 52% (4.27–7.58 GHz). The radiation patterns are bidirectional in both planes. This antenna can be part of various wireless communication systems.